Impact of annual bone loss and different bone quality on dental implant success - A finite element study - Linetskiy, Igor; Demenko, Vladyslav; Linetska, Larysa; Yefremov, Oleg (Computers in biology and medicine, 2017)
BACKGROUND: For dental implant success, experimentally established thresholds should limit bone stresses and strains. From these metrics, the ultimate functional load, which determines the implant load-carrying capacity, can be calculated. Obviously, its decrease due to bone loss shortens implant service life. A comparison of how bone loss affects the ultimate functional loads of various implants can provide the clinician with meaningful feedback concerning the suitability and longevity of implants. The aim of this study is to evaluate the lifetime of different dental implants placed in I-IV bone types on the basis of a comparison of their ultimate functional loads with consideration of the bone loss factor. METHOD: Von Mises stress and first principal strain distributions in bone-implant interface were studied and ultimate functional loads were calculated. Models of I-IV bone types were designed. 3.3 × 8.0 mm (A), 4.1 × 12.0 mm (B) and 4.8 × 14.0 mm (C) implants were analyzed at 10 levels of bone loss. Ultimate functional loads, which generated the ultimate von Mises stress and first principal strain in bone, were computed. RESULTS: For the implants A, B, and C placed in type I bone, ultimate functional load values were above 120.92 N experimental functional load, which corresponded to 10+, 10+, and 10 + years of service with 0.2 mm annual bone loss. For type II bone, the lifetime was 4, 10+, and 10 + years. For type III bone, the lifetime was 4, 5, and 5 years. For type IV bone, first principal strains were initially deleterious for all implants. CONCLUSIONS: In oral implantology, bone loss is an essential factor for implant longevity prognosis. While evaluating implant load-carrying capacity, clinicians should take into account the factor of implant longevity decrease.
Keywords: biologické modely; Alveolar Bone Loss; Dental Implants; výsledek terapie; zubní implantáty; Finite Element Analysis; Ultimate functional load; lidé; Models, Biological; Bone loss; Treatment Outcome; mechanický stres; Stress, Mechanical; Bone quality; biomechanika; resorpce alveolární kosti; Dental implant; analýza metodou konečných prvků; Finite element analysis; Biomechanical Phenomena; Humans